An Un-Historic Verdict : "Know thy army", and Other Essays - Durrani, M. Asad Lt. Gen. (Lahore Jang Publishers, 2001)
Compendium of selected previously published essays by Pakistani military appointee, intelligence director, attache to Germany, and envoy to the Kingdom of Saudi Arabia.
Include Notes
Keywords: Pakistan -- Politics and government